INOVASI LAYANAN KESEHATAN BERBASIS E-GOVERNMENT (Studi pada Puskesmas Kecamatan Kepanjen Kabupaten Malang) - Mindarti, Lely Indah; Juniar, Aryn Pratista Azaria (JPSI (Journal of Public Sector Innovations), 2018)
Health is considered an investment for the development of Indonesian people resources. Health is one ofÂ the important aspects of a country. Health becomes one of the welfare benchmarks in a country. Health is an obligation of every person to participate in realizing, maintaining and improving public health status as high as possible. The public is entitled to obtain optimal health services in accordance with the needs of the Government and health facilities is an obligation to be able to control and improve the health services available to the community. But now the public service in the field of health has not been said to be good. Until now the government is still improving to provide public services in the field of optimal health. There needs to be a link between government, business sector and society in creating an optimal service based on e-goverment. Because of these demands Puskesmas Kecamatan Kepanjen, Malang Regency to create and implement innovation programs related to health services applied ICT namely Sutera Emas ProgramÂ Â